INFLUENCE OF SOWING RATE AND PERIODS ON DRY MASS ACCUMULATION IN RYJIK VARIETIES (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
When analyzing the accumulation of dry mass in the varieties studied in the article according to development phases, the highest indicator falls on the legume planting phase; on October 20, on time, it was noticed that 10 million seeds were planted according to the norms.